Jointly created authority: a conversation analysis of how power is managed by parents and systemic psychotherapists in children's social care. Issue 3 (29th October 2018) - Watson, Rachel
Abstract : Social care settings provide a complex landscape for systemic psychotherapists, particularly in relation to issues of power that are particularly pervasive. Conversation Analysis (CA) was used as a research method to understand the detail of how systemic psychotherapists and parents work together in the safeguarding context. The study aimed to examine the power issues arising, and how they were being managed. CA literature, seen as a reminder of the centrality of 'talk as action', is used as a lens through which to present the findings, and the concept of authority as joint action is introduced. The findings of the study showed how systemic approaches, put to use through systemic techniques, can uniquely contribute to safeguarding work in contexts where issues of power prevail, with a particular emphasis on the importance of the concept of self‐reflexivity. Practitioner points: Notice and work with the complex circular ways that power issues arise in relationships in social care settings Use the concept of Jointly Created Authority to provide a relational frame for managing issues of power Revisit the concept of self‐reflexivity which is of primary importance to effective working in this context Develop understanding of how, using reflexive practice, adjusting responses in the moment can invite agency in clients 抽象: 共同创造的权威：对父母和系统心理治疗师在儿童社会关怀中如何管理权力的对话分析 社会关怀场景对于系统性心理治疗师来说是一个复杂的环境，特别是在尤其普遍存在的权力问题方面。本研究使用对话分析（CA）的研究方法，以了解系统性心理治疗师和父母如何在儿童保护的背景中一起工作的细节。该研究旨在研究出现的权力问题，以及如何应对这些问题。对话分析相关文献被视为对于"谈话即行动"的中心地位的提醒，用来作为展示调查结果的视角，并引入权威即共同行动的概念。该研究的结果表明，通过系统技巧实现的系统工作方法如何能够在权力问题普遍存在的情况下对儿童保护工作产生独特的帮助，并尤其强调自我反思概念的重要性。 对实务工作者的启示: 注意并处理通过复杂的循环方式在社会关怀场景中出现的关系权力问题 使用"共同创造权威"的概念为管理权力问题提供关系框架 重新审视自我反思的概念，对于在这种背景下有效工作至关重要 了解如何通过反思实践，及时调整回应，以激发来访者的主动性 Resumen: Autoridad creada conjuntamente: un análisis conversacional de cómo los padres y los psicoterapeutas sistémicos manejan el poder en la atención social de los niños Los entornos de atención social y protección a la infancia ofrecen un panorama complejo para los psicoterapeutas sistémicos, particularmente en relación con los problemas de poder que son particularmente generalizados. El Análisis Conversacional (CA) se usó como un método de investigación para comprender los detalles de cómo los psicoterapeutas sistémicos y los padres trabajan juntos en el contexto de la protección. El objetivo del estudio fue examinar los problemas de poder que surgen y cómo se estaban gestionando. La literatura de AC, vista como un recordatorio de la centralidad de "hablar como acción", se usa como una lente a través de la cual se presentan los hallazgos y se introduce el concepto de autoridad como acción conjunta. Los hallazgos del estudio mostraron cómo los enfoques sistémicos, puestos en uso a través de técnicas sistémicas, pueden contribuir de manera única a salvaguardar el trabajo en contextos donde prevalecen los problemas de poder, con un énfasis particular en la importancia del concepto de auto‐reflexividad. Puntos de implicación práctica: Observar y trabajar con las complejas formas circulares en que surgen los problemas de poder en las relaciones en entornos de atención social Usar el concepto de 'Autoridad creada conjuntamente' para proporcionar un marco relacional en el que administrar los problemas de poder Revisar el concepto de auto‐reflexividad, que es de primordial importancia para el trabajo efectivo en este contexto. Desarrollar la comprensión de cómo, utilizando la práctica reflexiva, ajustar las respuestas en el momento preciso puede promover la pro‐actividad en los clients